Students' Challenges and Strategies in Practicing English - Indonesian Sight Translation - Nandira Aulya Putri; Toneng Listiani; Dian Budiarti (Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to find out the challenges faced by students when they practice English-Indonesian sight Translation. In addition to the challenges, this study also explains the students’ strategies to pass the challenges. To find the same or similar answers and different answers related to this research, this study interviewed the students as the respondents so that this study categorized respondents into three categories in terms of grade. There are 2 high-achiever students, 2 middle-achiever students, and 2 low-achiever students who will be interviewed concerning their tips and approaches. The scores were obtained from the lecturer who taught the Simultaneous Interpreting course at the English Literature department of the State Islamic University in Bandung, in the 2024 academic year. The study found that there are three dominant challenges mentioned by the respondents and two dominant strategies mentioned. Many of them seemed to have difficulties in practicing English-Indonesian Sight Translation, such as lack of vocabulary knowledge, being rushed due to time limits, and unfamiliar types of documents. It is assumed that the strategies they used to minimize the mistake when they practice were the guess word meaning method, stay focused, and keep interpret the document, so that the students can minimize the mistake shown in front of the audience. The challenges faced and the strategies used by high achiever students are different from middle achiever and lowest achiever students. High achiever students use more strategies to deal with challenges so that the challenges faced are not too difficult.